(untitled) (Heritage, 2021)
The subject of this paper is theoretical and empirical research of students’ motivation, teaching focus and students’ and teachers’ roles in the teaching process of higher education. The research presented in the paper was conducted on a sample of two pedagogical faculties: the Preschool Teacher Training College in Kikinda in Serbia and the Faculty of Pedagogy in Pitesti, Romania during the 2019/2020 school year. The findings show that students’ motivation to learn is moderately high, and that internal motivation is more prevalent than external. Most of the students state that they take the role of participants in teaching process, and that their teachers take the role of a source of knowledge. The teaching focus, based on the students’ answers, is predominantly focused on the content of teaching. These results indicate a solid but not satisfactory picture of pedagogical practice. It is necessary to shift the focus of teaching to students, to develop a democratic climate ng in which teacher represents support of the learning process (the role of catalyst of the learning process), and to develop students’ initiative, independence and responsibility in learning, which strengthens the role of active, independent participants. To this statement also contributes the finding that the teaching focus on the sample in Romania was far more focused on students than in Serbia, and that the internal motivation of students in Romania wass far higher than the internal motivation of students in Serbia. Moreover, a relatively more favorable pedagogical picture of the faculties in Romania, in line with the statistically significant differences in relation to Serbia, is in line with the general picture of a country with a better socio-economic position and management (as an EU member). Therefore, the results of this study are in many ways interesting and relevant, and as such can be important to theorists and practitioners from a psycho-pedagogical, but also from the point of view of management in education.